Reaching Those Most at Risk for HIV Acquisition: Evaluating Racial/Ethnic Disparities in the Preexposure Prophylaxis Care Continuum in Baltimore City, Maryland. (15th August 2021) - Schumacher, Christina M.; Tao, Xueting; Chandran, Aruna; Fields, Errol; Price, Ashley; Greenbaum, Adena; Jennings, Jacky M.
Abstract : Background: Reducing HIV incidence requires addressing persistent racial/ethnic disparities in HIV burden. Our goal was to evaluate preexposure prophylaxis (PrEP) delivery, overall and relative to community need, among 7 clinical sites participating in a health department–led demonstration project to increase PrEP in Baltimore city, MD. Methods: PrEP care continuum stages (screened, indicated, referred, linked, evaluated, prescribed) were examined among HIV-negative individuals receiving services at participating sites between September 30, 2015 and September 29, 2019. Community need was defined using information on new HIV diagnoses (2016–2018). Differences in care continuum progression by demographics/priority population and comparison of demographic compositions between care continuum stages and new HIV diagnoses were examined using modified Poisson regression and χ 2 tests, respectively. Results: Among 25, 886 PrEP-screened individuals, the majority were non-Hispanic (NH) black (81.1%, n = 20, 998), cisgender male (61.1%, n = 15, 825), and heterosexual (86.7%, n = 22, 452). Overall, 31.1% (n = 8063) were PrEP-indicated; among whom, 56.8% (n = 4578), 15.6% (n = 1250), 10.8% (n = 868), and 9.0% (n = 722) were PrEP-referred, linked, evaluated, and prescribed, respectively. Among 2870 men who have sex with men (MSM), 18.7% (n = 538) were PrEP-prescribed. Across all groups, the highest attrition was between PrEP-referred and PrEP-linked. NH-black race (vs. NH-white) was independently associated with lower likelihood of PrEP prescription (aPR, 0.89; 95% confidence interval, 0.81 to 0.98 controlling for age/gender). Relative to the demographic composition of new HIV diagnoses, fewer NH-blacks (80.2% vs. 54.3%) and more NH-whites (10.7% vs. 30.3%) and MSM were PrEP prescribed (55.2% vs. 74.5%). Conclusions: This project showed promise delivering PrEP referrals and prescriptions overall and to MSM. Substantial improvement is needed to improve linkage overall and to decrease disparities in PrEP prescriptions among NH-blacks. Future work should focus on addressing service gaps that hinder PrEP utilization.